Specifics cryptographic currencies and their role in modern financial systems in terms of security - Voloshin, Vyacheslav (Collection "Information Technology and Security", 2018)
The paper presents results of the analysis and argumentation on the place of crypto currency in the modern world financial system. In this paper you can see ambivalence of conditions of crypto currency existence as the software solution, foremost according to the type of risks, which they provide for modern society, and risks, which determines of the uncertainty of their legal status. Based on direct and indirect data, it is shown that all types of crypto currency contain certain types of risks for financial and economic systems, in particular those related to cyber fraud, tax evasion outside the legal field of almost any state which include a possibility of currency transactions, money laundering by a criminal environment, impact on electronic communication systems, etc. The features of the understanding of the security functioning of cryptographic currencies as an alternative to modern cash were investigated. The role of the US Federal Reserve System and some of the world’s largest companies in the US, Europe and Japan has been analyzed with respect to the risks associated with the movement of crypto-currencies as of a product of the global information space. The argumentation is presented in favor of crypto currency, as a specific commodity, which does not yet have the properties of full-fledged money. By way of comparison, the calculation of cash mass movement dynamics in some countries has been performed and presented as one of the arguments for the countries’ readiness to safety switch to digital counterparts of money, as a means for intensification of the trade operations and the risks associated with it. The possibilities of the countries which are divided into three conditional groups, with reference to their susceptibility to crypto-currencies are clearly demonstrated. An attempt has been made to consider block-chain operations as a herald of fundamentally new relations in world trade, economics, based not on reciprocity but on parity relations, mutual helpfulness, i.e. opportunities that are offered only by block-chain operations. The conclusion has been made about the role and place of the crypto currency as a tool for the artificial stabilization of the world currency market through conscious manipulation of people’s needs in conditions when the global information space serves as an instrument for achieving the above goals, which refers to the violation of human rights.